PENTINGNYA SISTEM INFORMASI AKUNTANSI DAN PENGUNGKAPAN PADA KUALITAS LAPORAN DALAM AKTIVITAS PERBANKAN (SEBUAH KAJIAN KONSEPTUAL) - ARDYA FIRSTA, DEFRI (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to knowing the importance of accounting information systems and the quality of the disclosure statement in banking activities by using the methods of literature this study describes the importance of a accounting information system and disclosure on the quality of the report on banking activity. Then, this study also serves to increase public understanding of the importance of accurate and relevant reports related to banking activities. Finally, the accounting information system will require financial statements prepared in accordance with the requirements of banks to be disclosed to the public. The preparation of financial statements should be based on procedural inputting, processing the data to the form of presentation that had used accounting information system must also be concise and packed in the interests of public disclosure. There are several key factors that affect the quality of the disclosure and reports using accounting information systems in banking activities, that is accuracy, timeliness, completeness, conciseness of data, and suitability of statements. Keyword: Accounting Information System, Disclosure, Quality of Report, Banking Activities